OPTIMILIZATION OF LOCALLY-GENERATED REVENUE OF ACEH TIMUR THROUGH SHARIA TOURISM DEVELOPMENT - Astina, Chahayu (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2020)
Province of Aceh has special autonomy rights accordance with Law Number 18 of 2001 with Islamic Shariah being the material written in the form of Qanun (set of syariah regional regulations) first. One of the objectives to be achieved in the implementation of regional autonomy is to bring regional independence. To achieve regional independence, increasing Locally-Generated Revenue (PAD) is one of the fiscal instruments that cannot be avoided in developing the economy and the welfare of the people. The purpose of this study is 1) To determine the potential of PAD sourced from Regional Taxes and Regional Retribution in East Aceh Regency; 2) To analyze the strategies carried out by the East Aceh Regional Government in optimizing regional tax and retribution revenues from potential tourism areas in the future. By using a qualitative research approach, based on the results of field observations, Focus Group Discussion (FGD) and interviews with expert sources, the results are obtained that the potential of PAD sourced from Regional Tax and Retribution in East Aceh Regency is still minimal. There are no tourist areas, entertainment venues, restaurants that are in line with the category of regional taxpayers and local user fees, making the source of income for PAD unable to be the main source of income for East Aceh Regency. The next result is the strategy carried out by the East Aceh Regional Government in optimizing regional tax and levies revenue from potential tourism areas, starting with the opening of tourist areas, especially for coastal areas in the form of socialization and management of tourism area management through third parties (private) and the East Aceh Regency government. For the implementation of the taxpayer for the entertainment tax sector in the PAD can not be implemented at this time, but it is hoped that the success of the government will be the basis for future PAD resources.